In vitro evaluation of the root canal cleaning ability of plant extracts and their antimicrobial action - Edja Maria Melo de Brito Costa; Augusto Pierry de Araújo Evangelista; Ana Cláudia Dantas de Medeiros; Fábio Roberto Dametto; Rejane Andrade de Carvalho (Sociedade Brasileira de Pesquisa Odontológica, 2012)
This in vitro study evaluated both the antimicrobial activity and the root canal cleaning ability of plant extracts used in irrigation solutions. The antimicrobial activities of the aroeira-da-praia (Schinus terebintifolius Raddi) and the quixabeira (Syderoxylum obtusifolium Roem & Schult) hydroalcoholic extracts, of 2.5% sodium hypochlorite (NaOCl) and of 0.12% chlorhexidine (positive control) against Enterococcus faecalis were tested with the agar well diffusion method. The level of root canal cleanliness was examined by scanning electron microscopy (SEM). Twenty one single-rooted human teeth were divided into three groups according to the irrigation solution applied: 1) 50% aroeira-da-praia; 2) 50% quixabeira and 3) a combination of 2.5% sodium hypochlorite + 17% EDTA. All solutions tested demonstrated antimicrobial activity against Enterococcus faecalis. The SEM analysis revealed that higher and lower degrees of surface cleaning were observed, in the three groups, respectively for the coronal and apical thirds, in that quixabeira showed the greatest efficiency in removing the smear layer in the apical third. All the agents tested presented antimicrobial activity against E. faecalis. None, however, was able to completely remove the smear layer of the dentinal surface in the different thirds of the root canal. The results suggest that the analyzed plant extracts may represent a new therapeutic option in the list of alternative agents available for endodontic treatment.